Exploration of the structure-property relationship of push-pull based dyads for single-molecule organic solar cells. (November 2019) - Labrunie, Antoine; Habibi, Amir Hossein; Dabos-Seignon, Sylvie; Blanchard, Philippe; Cabanetos, Clément
Abstract: The synthesis, characterization and use of three donor-σ-acceptor molecular dyads as organic photoactive layer are reported herein. Based on push-pull π-conjugated systems, the donor moiety is connected through a non-conjugated σ-linker to a PC61 BM derived block. Three different π-connectors, constituting the push-pull unit, namely a bithiophene (BT ), a thienothiophene (TT ) and a cyclopentadithiophene (CPDT ) units were selected to assess the impact of the chemical bridging (CPDT ) or fusing (TT ) on the electronic, electrochemical and therefore photovoltaic properties. Hence through a better understanding of the structure-property relationships, power conversion efficiencies exceeding the symbolic percent have been reached in single-molecule organic solar cells. Graphical abstract: Image 1 Highlights: Simple chemical modifications to improve the efficiencies of single-molecule organic solar cells. Better understanding of the structure-property relationships. Fabrication and characterization of single-molecule organic solar cells (SMOSCs).